(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine The Financial Strategies for Budgeting Allowances for Grade 12 Working Students and help the working students with the help of proposed intervention and remediation. It was figured out that the Budgeting Daily allowances are the impacts that affect their financial strategies. Furthermore, results showed that Mental Health is the challenge that working students face. Budgeting Daily allowance inadequate funds are the advantages and the disadvantages of grade 12 working students, and with the help of proposed recommendations to the disadvantages, it lessened the challenges of grade 12 working students. The respondents of the study were 50 selected grade 12 working students. The selected respondents are those who have a connection to our study, which is all about the financial strategies of grade 12 working students. Based on the results of the study, the proposed intervention and remediation of the financial strategies to the grade 12 working students addressed above the cited impacts and helps working students in terms of (1) Budgeting Daily Allowance – it helps the students to recognize the expenses they must pay for them to allocate their money. (2) Healthy Mental Health - It helps the students have a better sense of relief and calmness, knowing that they have a proper financial strategy. (3) Inadequate Funds – It helps the students understand that having inadequate funds means having no financial means to pay expenses. The researchers recommend to working students that they should consider financial strategies as a guide and engage easily with their allowance. Working students should consider financial strategies to meet their goals of being able to pay for their expenses. Working students should also consider financial strategies as a motivation to prioritize their needs above anything else. The research helps researchers in a way that throughout the study, they acquire information that helps them to navigate the impacts of financial strategies on working students. Future researchers should recommend Budgeting Daily Allowances to help working students manage their financial strategies.